Dzieje Polski - Zak, Jan.; Topolski, Jerzy (Warszawa : Wydawnictwo Naukowe PWN, 1993)
A comprehensive history of Poland from pre historical times up to 1795.
v.1. Do roku 1501 -- v.2. 1501-1795 -- v.3. 1795-1918.
Editors vary.
Maps also in pockets.
Includes bibliographical references and indexes.
Keywords: Poland -- History